Constructing the image of Islam in contemporary Russian print media: the language strategies and politics of misrepresentation - Ragozina, Sofya (Religion, state & society, 2020)
This article examines Russian print media coverage from 2010 to 2016, specifically newspaper articles, addressing topics related to Islam. It seeks to identify the main linguistic strategies employed to construct a negative image of Islam within a broader discursive strategy of differentiation between ‘radical’ and ‘traditional’ Islam. The research is based on critical discourse analysis and corpus linguistics, and draws on a corpus containing 18,308 articles from six national newspapers: Nezavisimaia Gazeta, Kommersant, Komsomolskaia Pravda, Moskovskii Komsomolets, Rossiiskaia Gazeta, and Novaia Gazeta. Through an analysis of the lexical compatibility patterns of the lexeme ‘Islam’ (e.g. ‘Islam + verb’, ‘Muslim/Islamic + noun’), the article identifies the four most obvious discursive strategies aimed at creating a negative image of Islam: 1) defining ‘correct’ Islam; 2) homogenising Muslims via ‘big numbers’; 3) criminalising neutral connotations (e.g. ‘Muslim celebration’); 4) misunderstanding specific Islamic terms.